Association of Quantitative Characteristics with Growth Hormone Gene (GH Gene) in Kerinci Duck Using PCR-RFLP Method - Amalia Fildzah Ghassani; Depison Depison; Helmi Ediyanto (Buletin Peternakan, 2022)
This study aims to determine the association of quantitative characteristics with growth hormone gene (GH gene) in kerinci duck using PCR-RFLP method. Samples total used was 96 Kerinci ducks consisting of 43 males and 53 females and 96 blood samples. DNA was extracted using the protocol Genomic DNA Purification Kit from Promega and then amplified by PCR using a pair of primers5'-CAA GGA ACA GAG GGT TTC CA-3' and Revers : 3'-GGG AGA TAG GGC AAA CAT CA-5', with a length of product 855 bp. The amplification product was cut using restriction enzyme AluI with the AG↓CT cutting site. Growth hormone/AluI fragments of Kerinci duck were electrophoresed using 1.5% agarose gel and visualized using doc gel. Data collected includes body weight, weight gain, body measurements, and blood of Kerinci ducks. The differences in body weight, body weight gain, and body measurements, as well as differences in body weight between genotypes were tested by T-test. The determinants of the size and shape of Kerinci duck were analyzed using PCA. This study showed that the body weight, weight gain, and body sizes of male Kerinci ducks were significantly different (P<0.05) than female Kerinci ducks. The Kerinci duck GH|AluI gene is polymorphic with three genotypes, i.e, +/+ of (49%), +/- of (39.6%), and -/- of (11.5%), and two alleles, namely (+) by 69% and (–) by 31%. Conclusion: body weight, weight gain, and body sizes of male Kerinci ducks were higher than female. The size identifier of male and female Kerinci ducks were sternum, shank lengh, and shank circumference, while shape identifier was wing length. GH Genes|AluI in Kerinci duck is polymorphic. GH gene |AluI of Kerinci ducks was associated with body weight, weight gain, and body measurements, and the best is the genotype (+/+).